Exchange Dynamics Reveal Significant Accumulation of Dimethylated Sulfur by Mediterranean Benthic Communities - Burdett, Heidi L. (Frontiers in Marine Science, 2017)
One fifth of Mediterranean waters can be classified as shelf – much higher than the global average. Consequently, the shelf / coastal zone plays a proportionally greater biogeochemical role than in the major oceans, including the support of a wide range of range of endemic or culturally important species and ecosystems. However, despite their known importance in regulating ecosystem function and the marine sulphur cycle, our understanding of the dynamics of dimethylated sulphur compounds such as dimethylsulphide (DMS) and dimethylsulphoniopropionate (DMSP) in Mediterranean benthic habitats is limited. Here, a community-level approach was adopted to quantify DMS and DMSP dynamics in Mediterranean ecosystems including seagrass (Posidonia oceanica) meadows, coralligène (an algal carbonate reef found along the Mediterranean shelf) and macroalgal stands. It was found that P. oceanica and coralligène are likely to act as significant benthic stocks of DMSP in the coastal / shelf environment. ‘Hotspots’ of water column DMS and DMSP processing were observed where net benthic production was high (e.g. P. oceanica meadows), demonstrating that benthic communities are able to modify DMS biogeochemistry in the overlying water column. High variability between, and within, habitat types illustrates the importance of ecosystem structure and light availability in determining benthic DMS and DMSP accumulation, and highlights a previously under-appreciated complexity in benthic dimethylated sulphur dynamics.